2014
DOI: 10.3233/jad-132768
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cortical Thinning and Cerebrospinal Biomarkers Predict Worsening Daily Functioning Across the Alzheimer's Disease Spectrum

Abstract: Background Impairment in instrumental activities of daily living (IADL) heralds the transition from mild cognitive impairment (MCI) to dementia and is a major source of burden for both the patient and caregiver. Objective To investigate the relationship between IADL and regional cortical thinning and cerebrospinal fluid (CSF) Alzheimer disease (AD) biomarkers cross-sectionally and longitudinally in clinically normal (CN) elderly, MCI, and mild AD dementia subjects. Methods Two hundred and twenty nine CN, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 23 publications
7
41
0
Order By: Relevance
“…As reported previously [39, 40], high-Aβ MCI have decreased ACT when compared to low-Aβ CN. However, ACT was less discriminant for high-Aβ MCI than the other biomarkers we studied.…”
Section: Discussionsupporting
confidence: 80%
“…As reported previously [39, 40], high-Aβ MCI have decreased ACT when compared to low-Aβ CN. However, ACT was less discriminant for high-Aβ MCI than the other biomarkers we studied.…”
Section: Discussionsupporting
confidence: 80%
“…Baseline biomarker measures as a predictive factor of functional decline is a novel area of research, with very few studies having explored such relationships and of those comparable; our findings are congruent [14][15][16][41][42][43]. Two separate studies found regional cortical thinning and decreased CSF A1-42 to predict IADL decline across the AD spectrum [15,41].…”
Section: Discussionsupporting
confidence: 74%
“…Two separate studies found regional cortical thinning and decreased CSF A1-42 to predict IADL decline across the AD spectrum [15,41]. Likewise, correlations between cerebral atrophy and IADL decline in MCI individuals have been reported [14], with rate of decline found to increase three fold in APOE-4 positive individuals [42].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, a subgroup of these subjects underwent magnetic resonance imaging (MRI), which showed that impaired performance was associated with inferior temporal cortical thinning in clinically normal subjects. This finding aligns with other studies suggesting that cortical thinning may be one of the earliest biomarker correlates of cognitive and functional decline (13, 14), and further supports the use of sensitive performance measures for the assessment of decline in the earliest stages of the disease.…”
Section: Is It Clinically Relevant?supporting
confidence: 90%